The signal complexity of international alliances in pre-IPO firms. (9th November 2020) - Smith, Adam W.; Moghaddam, Kaveh; Pezeshkan, Amir
Applying signalling theory to firm valuation, we theorise that firms engaging in international alliances produce complex signals. We match archival data on attributes and the alliancing activities of pre-IPO firms to construct a sample of 106 technology companies receiving funding venture capital. We then conduct ANOVA and regression analysis. The use of international alliances, the structure of the alliance, and alliance formation in institutionally challenging regions all positively affect investors' valuations of young ventures. These findings suggest that in addition to providing access to resources or markets, alliances can serve as signals about focal firm characteristics, alerting venture capitalists to the growth potential of pre-IPO ventures. A venture's ability to form an international alliance, particularly in an institutionally challenging region, signals a level of managerial adeptness and venture resource quality/quantity to investors.